Theodicy in Islamic Philosophy and Scholasticism: An Examination of the Problem of Evil in the Thought of Aquinas and Muthahhari - Firnando, Hero Gefthi (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
The issue of evil pertains to the intricate relationship between the existence of God and the prevalence of wickedness in the world. This conundrum has been a focal point of numerous scholars and intellectuals for centuries, giving rise to skepticism, agnosticism, and atheism. The ramifications of these philosophical and theological dilemmas present substantial challenges to the belief in a divine being.In this paper, we seek to fortify theistic arguments in response to these contentious issues. To this end, we adopt a philosophical approach that focuses on the theodicy of two major figures: Murtadha Muthahhari and Thomas Aquinas.This endeavor is intended to fulfill rational criteria and encourage individuals to rethink their negative views on the existence of God. As a result, both philosophers—Thomas Aquinas and Murtadha Muthahhari—strengthen theistic arguments through the concept of theodicy relating to God's justice. The aforementioned philosophers concur that the fundamental cause of evil can be traced to four primary factors: the existence of God as the creator of all things, the existence of evil as a reality, the existence of humans who possess freedom and moral responsibility, and the existence of a dynamic nature with its unique laws and development.